Increased Adipose Tissue Fibrogenesis, Not Impaired Expandability, Is Associated With Nonalcoholic Fatty Liver Disease. Issue 3 (22nd June 2021) - Beals, Joseph W.; Smith, Gordon I.; Shankaran, Mahalakshmi; Fuchs, Anja; Schweitzer, George G.; Yoshino, Jun; Field, Tyler; Matthews, Marcy; Nyangau, Edna; Morozov, Darya; Mittendorfer, Bettina; Hellerstein, Marc K.; et al.
Abstract : Background and Aims: It is proposed that impaired expansion of subcutaneous adipose tissue (SAT) and an increase in adipose tissue (AT) fibrosis causes ectopic lipid accumulation, insulin resistance (IR), and metabolically unhealthy obesity. We therefore evaluated whether a decrease in SAT expandability, assessed by measuring SAT lipogenesis (triglyceride [TG] production), and an increase in SAT fibrogenesis (collagen production) are associated with NAFLD and IR in persons with obesity. Approach and Results: In vivo abdominal SAT lipogenesis and fibrogenesis, expression of SAT genes involved in extracellular matrix (ECM) formation, and insulin sensitivity were assessed in three groups of participants stratified by adiposity and intrahepatic TG (IHTG) content: (1) healthy lean with normal IHTG content (Lean‐NL; n = 12); (2) obese with normal IHTG content and normal glucose tolerance (Ob‐NL; n = 25); and (3) obese with NAFLD and abnormal glucose metabolism (Ob‐NAFLD; n = 25). Abdominal SAT TG synthesis rates were greater ( P  < 0.05) in both the Ob‐NL (65.9 ± 4.6 g/wk) and Ob‐NAFLD groups (71.1 ± 6.7 g/wk) than the Lean‐NL group (16.2 ± 2.8 g/wk) without a difference between the Ob‐NL and Ob‐NAFLD groups. Abdominal SAT collagen synthesis rate and the composite expression of genes encoding collagens progressively increased from the Lean‐NL to the Ob‐NL to the Ob‐NAFLD groups and were greater in the Ob‐NAFLD than the Ob‐NL group ( P  < 0.05). Composite expression of collagen genes was inversely correlated with both hepatic and whole‐body insulin sensitivity ( P  < 0.001). Conclusions: AT expandability is not impaired in persons with obesity and NAFLD. However, SAT fibrogenesis is greater in persons with obesity and NAFLD than in those with obesity and normal IHTG content, and is inversely correlated with both hepatic and whole‐body insulin sensitivity.